The Relationships of Knowledge, Attitude, and Smoking Cessation Promotion Behavior for Smoker Patients among Air Force Student Nurses - คำรัตน์, จิรภิญญา (Journal of The Royal Thai Army Nurses, 2019)
This study aimed to examine level and relationships of knowledge, attitude and smoking cessation promotion behavior for smoker patients among Air Force student nurses. Samples were 86 Air Force student nurses. Questionnaires composed of demographic data, knowledge, attitude and smoking cessation promotion behavior questionnaires. Data were analyzed by descriptive statistic and Pearson product moment correlation coefficient. The results showed that majority of the samples’ knowledge level of smoking was good ( = 11.17, S.D. = 1.64), their attitude was a good level ( = 65.52, S.D. = 5.13), and smoking cessation promotion behavior for smoker patients was a medium level ( = 19.58, S.D. = 3.10). The findings of the relationships revealed that knowledge and attitude were significantly correlated to smoking cessation promotion behavior for smoker patients (r = 0.32, 0.36, p<0.05, respectively). These results can be used to guide learning process about tobacco control for nursing student in the future.